Resolving the Commitment Conflict of TeacherAcademic Entrepreneurship in Research Universities in the United States - YAO Lin; LI Ting; DENG Yanhong (Jiaoshi jiaoyu xuebao)
Research universities in the United States regard teacher academic entrepreneurship as an important way to extend the knowledge production chain, to promote the achievement transformation and to fulfill the social service function. However, teachers play a dual role as scholars and entrepreneurs in the process of academic entrepreneurship. Moreover, due to the cross-impact of academic culture and entrepreneurial culture, as well as the blurred boundary between traditional functions and academic entrepreneurship in research universities, teachers therefaces commitment conflicts in the process of academic entrepreneurship. The conflict of commitment is manifested in three aspects: teaching, research and social service. In addressing the commitment conflicts faced by teachers in academic entrepreneurship, Research universities in the United States adopt a comprehensive approach focusing on system construction, cultural atmosphere, role identity, duty boundaries, and distribution mechanisms. They establish a prior approval and post-disclosure system, foster a symbiotic environment where academic culture and entrepreneurial culture coexist, adhere to multiple norms of acade-mic and entrepreneurial work, and create a benefit-sharing and distribution mechanism. This approach aims to transform conflicts into mutual benefit and win-win outcomes, better balancing teachers' responsibilities and commitments in academic entrepreneurship, teaching and research, and social ser-vice, ultimately facilitating their transition into academic entrepreneurs.